THE USE ENGLISH ISLAMIC SONGS TO IMPROVE STUDENTS’ LISTENING ACHIEVEMENT - Dewi Sartika (Universitas Islam Ogan Komering Ilir Kayuagung, 2017)
Listening plays important role in communication. In fact, students had troubles in understanding someone spoke. The aim of this study was to improve students listening skill by using Islamic English songs. The method was a classroom action research that consisted of pretest, two cycles, and posttest. Each cycle consisted of four steps: planning, action, evaluation, and reflection. The subject was the second semester of English Language Education Department of FKIP Islamic University of Ogan Komering Ilir that consisted of 24 students. The instrument was a written test and analyzed by mean score formula. The result showed that in the pretest, the students’ mean score was 51.46 (low), in cycle 1, the students’ mean score was 61.46 (moderate), and in cycle 2, the students’ mean score was 70.29 (moderate). In the posttest, the students’ mean score had improvement (80.13) which was in good category. Therefore, it could be concluded that the use of English Islamic songs improved the second-semester students’ listening skill. English Islamic songs stimulated students to listen to something so that they could identify the words and comprehend the content of the songs well